PENGARUH PENGGUNAAN MEDIA FLIPBOOK TERHADAP HASIL BELAJAR BAHASA INGGRIS PESERTA DIDIK KELAS TINGGI DI SD NEGERI 060786 - Monika Juliana Bai Sipangkar; Dody Feliks Pandimun Ambarita; Tiarnita Maria Sarjani Br. Siregar; Albert Pauli Sirait; Edizal Hatmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of using Flipbook media on students’ learning outcomes in English learning for 5th grade students at SD Negeri 060786 in the 2025/2026 academic year. The research employed a pre-experimental method using a one-group pretest-posttest design. The research sample consisted of all 5th grade students at SD Negeri 060786, selected through a total sampling technique, resulting in 18 students as participants. The research instrument was a set of 22 multiple-choice questions. The data analysis results indicated an improvement in students’ average learning outcomes, increasing from 41 in the pretest to 80 in the posttest. The hypothesis testing using the Wilcoxon Signed Rank Test showed a significance value of 0.001 (sig < 0.05), indicating that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Therefore, it can be concluded that the use of Flipbook media has a significant effect on students’ learning outcomes in English learning for 5th grade students at SD Negeri 060786 in the 2025/2026 academic year.